The Influence of Work Motivation, Work Discipline, Organizational Commitment, and Compensation on Organizational Citizenship Behavior - Liana, Siska; Endratno, Hermin; Darmawan, Akhmad; Rahmawati, Ika Yustina (PT FORMOSA CENDEKIA GLOBAL, 2025)
The purpose of this study is to investigate the impact of work motivation, discipline, and organizational Commitment, and Compensation Irganizational Citizenship Behavior. This study employs a quantitative technique. This study's sample included 103 personnel from Banyumas Regency's Population and Civil Registration Service. Sampling used a saturated sample method (census). This study collected data through the use of a questionnaire. The data was analyzed using SPSS 26. The results of the investigation revealed that work motivation had a positive and significant effect on OCB, work discipline did not affect OCB, organizational commitment did not affect OCB, and compensation has a favorable and considerable effect on OCB.